Solution of fractional order integro-differential equations by two semi-analytical methods - Yisa*† , B.M.; Yusuf†, Z.B. (International Journal of Mathematical Analysis and Modelling, 2023)
This paper is concerned with the solution of fractional order integro-differential equations where the fraction order,